Влияние температуры подложки на прочностные характеристики покрытий, полученных методом электроискрового легирования - Мазанко, В.Ф.; Храновская, Е.Н.; Иващенко, Е.В.; Ворона, С.П. (Видавничий дім "Академперіодика" НАН України, 2007)
The influence of temperature of a processable substrate on the strength characteristics of coverings obtained by the method of ESA is investigated by using the microstructural microdurometrical analysis. It is established that a decrease of the temperature of a substrate allows one to increase the thickness of the strengthened layer by 2–5 times and the microhardness by 1.5–2.5 times depending on a material of electrodes. The increase of corrosion stability of coverings by more than 1000 times in relation to a processable material in an unconfigured state is revealed. It is supposed that this effect can be caused by the formation of a liquid-like structure of a covering.